Cardio-oncology in advanced prostate cancer - Chen, Kenneth; Wong, Ting Hong; Tan, Yu Guang; Tay, Kae Jack; Tan, Wei Chong; Chan, Johan; Ho, Henry; Cheng, Christopher; Teoh, Jeremy Yuen-Chun; Chiu, Peter Ka-Fung; Wang, Hung Jen; Saad, Marniza Binti; et al. (Frontiers in Oncology, 2024)
Treatment intensification with androgen deprivation therapy (ADT) and androgen receptor pathway inhibitors (ARPi) have led to improved survival in advanced prostate cancer. However, ADT is linked to significant cardiovascular toxicity, and ARPi also negatively impacts cardiovascular health. Together with a higher prevalence of baseline cardiovascular risk factors reported among prostate cancer survivors at diagnosis, there is a pressing need to prioritise and optimise cardiovascular health in this population. Firstly, While no dedicated cardiovascular toxicity risk calculators are available, other tools such as SCORE2 can be used for baseline cardiovascular risk assessment. Next, selected patients on combination therapy may benefit from de-escalation of ADT to minimise its toxicities while maintaining cancer control. These patients can be characterised by an exceptional PSA response to hormonal treatment, favourable disease characteristics and competing comorbidities that warrant a less aggressive treatment regime. In addition, emerging molecular and genomic biomarkers hold the potential to identify patients who are suited for a de-escalated treatment approach either with ADT or with ARPi. One such biomarker is AR-V7 splice variant that predicts resistance to ARPi. Lastly, optimization of modifiable cardiovascular risk factors for patients through a coherent framework (ABCDE) and exercise therapy is equally important. This article aims to comprehensively review the cardiovascular impact of hormonal manipulation in metastatic hormone-sensitive prostate cancer, propose overarching strategies to mitigate cardiovascular toxicity associated with hormonal treatment, and, most importantly, raise awareness about the detrimental cardiovascular effects inherent in our current management strategies involving hormonal agents.